(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Very late antigen 4 (VLA4) integrin facilitates the immune cells migration to central nervous system (CNS) through blood brain barrier (BBB), so the polymorphism in this gene may be considered as genetic risk factor for multiple sclerosis (MS) occurrence. It may interact with the responsiveness level of Natalizumab. Objective: To show if VLA4 single nucleotide gene polymorphism (SNP) (C-269-A) considered as genetic predisposition factor for MS and if have a role in Natalizumab (Tysabri) drug non-responsiveness. Methods: Sixty-six (66) person with MS and 60 healthy persons involved in this study, their ages were range from 14 to 67 years. They attended to seek treatment in the MS outpatient’s clinic, at Baghdad Teaching Hospital, Medical City Complex from December 2018 to March 2020. Patient were divided into two group; resistant group (34) and response group (32). The VLA-4 SNP polymorphism investigated by sequence specific primer polymerase chain reaction (SSP-PCR) technique. Results: The VLA4 gene SSP-PCR genotyping revealed no significant differences between patients and control group also between responder patients and non-responder to Natalizumab. Conclusion: VLA-4 polymorphisms at the level of SNP at positions 269 (C/A) have no role in MS susceptibility or Natalizumab responsiveness. Keywords: MS, Natalizumab, VLA-4 Citation: Khaliel AH, Abbas AA, Hatem AO, Abdulamir AS. The impact of Very Late Antigen 4 polymorphism on drug responsiveness in patients with multiple sclerosis initiation. Iraqi JMS. 2022; 20(1): 83-89. doi: 10.22578/IJMS.20.1.11